Contribution of the study of the styloid prominence in the posterior tympanic cavity - Garcia, P. J.; Tamega, O. J.; Soares, J. C.; Piffer, C. R.; Zorzetto, N. L. (My University, 1982)
70 human temporal bones were analyzed with the aid of an otologic microscope. The styloid prominence was found to be extremely variable in shape, location and occurrence. Depending on the degree of development, the prominence establishes important relationships with the sinus tympani, with the fossula of the cochlear fenestra, and with the suprapyramidal recess. Serial sections were used to study the relationship of the styloid process with the facial nerve inside the bony mass of the mastoid portion of the temporal bone.
Keywords: auditory system; bone; normal human; styloid process; surgical anatomy; tympanic cavity; Ear, Middle; Female; Humans; Male; Temporal Bone